المستوى الدلالي في رثاء الإمام الحسين بن علي (ع) في العدوتين (المغربية والأندلسية) - كمالجو مصطفى; عبدالواحد حلفة ناطق (Journal of College of Education, 2020)
The semantic level is one of the linguistic studies of linguistics, Which appeared earlier in the Arab scholar, such as Al_kalil, syboyeh and other scholars, and the semantic level of the four linguistics levels besides the vocal level, the morphological level and the syntactic levels, the semantic level looks at the relationships between the signifier and the signified in a group semantic relationships consisting of (verbal joint, tandem and contradictions) as well as looking between the word and it’s relationship to the meaning, and the significance is that it is a science that reveals the words in the text in terms of stating their meaning in the terms of the private meaning and the general meaning, i. e explaining the intent of behind choice of pronunciation,. Each of these semantic relationships (joint, tandem and contact) Will be shown in terms of significance in The semantic level in the lamentations of Imam Hussein bin Ali, peace be upon him, the Moroccan and Andalusian regionsBy his author professor safaa Abdullah Burhan Al_Gharabwi